Whom to hire and how to coach them: a longitudinal analysis of newly hired salesperson performance. Issue 2 (2nd April 2020) - Bolander, Willy; Satornino, Cinthia B.; Allen, Alexis M.; Hochstein, Bryan; Dugan, Riley
Abstract: Salesperson hiring decisions are critical for firms, and managers typically accept one of two viewpoints regarding optimal hiring strategies. The first asserts that prior sales experience allows new salespeople to perform immediately upon hire and represents a valuable hiring heuristic. The second believes lack of prior experience allows managers to mold new salespeople to the hiring firm's needs. Further complicating matters, formal sales education programs are gaining in popularity and may represent an alternative hiring heuristic for sales managers. Using unique multisource data (from both B2B and B2C firms), the authors explore the effects of these hiring heuristics in driving salespeople's longitudinal performance trajectories, along with the moderating role of post-hire manager coaching behaviors. Results of the longitudinal growth models show the distinct and opposing effects of each hiring heuristic and coaching strategy. The authors also identify critical areas of future research and managerial practice.